Carbon dioxide emissions from industrial processes and product use are a non-ignorable factor in China’ s mitigation - Liting Hu; Xiaoyi Hu; Bowei Li; Liya Guo; Di Chen; Yang Yang; Mengyue Ma; Xinhe Li; Rui Feng; Xuekun Fang (Communications Earth & Environment)
Abstract China, the largest carbon dioxide (CO2) emitter in the world, is committed to achieving carbon neutrality by 2060. However, the characteristics and driving factors of the CO2 emissions from industrial processes and product use (IPPU) in China have been unclear. Here, using the most comprehensive statistics of 18 industrial productions and 2 product uses during 2000–2020, we find China’s IPPU CO2 emissions reached 1628 million metric tons (Mt) in 2020, which were 3.0%–6.5% higher than estimates from other studies. Compared to previous studies identifying main driving factors of combined CO2 emissions from fossil-fuel and IPPU, we show that the main indicators of China’s IPPU emissions growth was the per capita construction area during 2000–2020 (94%). We construct a comprehensive provincial IPPU emission inventory based on the up-to-date provincial-level statistics, identifying the key mitigation regions in China. This study reveals China’s IPPU emissions are the non-ignorable factor in China’s carbon mitigation.